Performance Characteristics of Savonius Wind Turbines With Variations Air Gaps in Supporting the Development of Renewable Energy - Hermawan, Baktiyar Mei; Sumarno, F. Gatot; Prasetyo, Totok; Sahid, Sahid; Roihatin, Anis; Aulia, Nur Fatowil; Surindra, M. Denny; Mulyono, Mulyono; Sofiani, Gizella; Putri, Tania Prameswari; Ariyanto, Wahyu (Eksergi, 2023)
To overcome the occurrence of an energy crisis in the future, an innovation / invention of energy that is environmentally friendly and energy sources will not run out in the future. Energy sources that are environmentally friendly and their potential when developed is very large, one of which is energy sources derived from wind energy. This study aims to determine the effect of wind speed on the performance of wind turbines. To find out the performance characteristics of wind turbines with variations in air gaps. The research method begins with the design / design of the wind turbine, then continues the manufacturing stage, the assembling and installation stage, the testing of tools and analysis, the tests carried out include testing the performance characteristics of the wind turbine. The parameters measured in this study are rotation, torque as well as calculating the kinetic power produced, TSR and CP. The test results conducted showed that the 200 mm air gap Savonius wind turbine with a value of CP = 0.02480-0.15658 had optimum work at low wind speeds (4 m / s). Meanwhile, the 170 mm airborne Savonius wind turbine with a value of CP = 0.00593-0.14668 has optimum work at high wind speeds (8 m / s to 9 m / s). Keywords- wind turbine savonius, air gap, coefficent of power.